A New SNPs at 3’UTR Region of calpain 1 gene and its association with growth and meat quality traits in beef cattle - Dairoh, D.; Jakaria, J.; Ulum, M. F.; Sumantri, C. (Journal of the Indonesian Tropical Animal Agriculture, 2022)
The objective of this study was to evaluate single nucleotide polymorphisms (SNP) in the 3'UTR region of CAPN1 gene by direct sequencing technique in beef cattle and its influence on growth and meat quality of the contrast mode ultrasound image in Bali cattle. The numbers of beef cattle used were Bali cattle (n=52 heads) which compared to purebred Belgian Blue (n=30 heads), Limousine (n=14 heads), Wagyu (n=7 heads), and PO (n=10 heads). Genetic diversity data were obtained from calculations by PopGen 1.32 software. Ultrasound imaging of the thoracic longissimus dorsi muscle in Bali cattle was carried out between the 12 − 13 ribs, and the sonogram was analyzed by Image-J NIH software. The result shown that 3’UTR of CAPN1 gene was found in six discovery SNPs that polymorphic in Bali cattle, they were g.15284 C>T, g.15347 T>G, g.15525 G>A, g.15853 G>A, g.15905 G>A, g.15915 G>A and Indel mutation was polymorphic in Bali cattle, Belgian Blue, Limousine, and PO. There was no association between these SNPs and growth traits. However, SNP g.15525 G>A was significantly associated (P<0.05) with a backfat thickness (BFT) in Bali cattle. In conclusion, the CAPN1 gene in Bali cattle is a candidate for Marker Assisted Selection (MAS) related to meat quality.